Hubungan Kosakata dengan Menulis Puisi (Korelasi Kelas V SD Negeri 22 Jeppe’e Kabupaten Bone) - Darmawati Darmawati; Rukayah Rukayah; Firdaus Firdaus (STKIP Andi Matappa Pangkep, 2022)
This research isÂ quantitative research with the type of correlational research which aims to determine: (1) a description of the vocabulary mastery of fifth grade students of SD Negeri 22 Jeppe'e, Tanete Riattang Barat District, Bone Regency, (2) an overview of the students' poetry writing skills V, (3) the relationship between vocabulary mastery and the ability to write poetry in fifth grade elementary school students. The population in this study were all fifth grade students with a total of 36 students, with saturated sampling technique. Data collection techniques using tests. Data analysis techniques with descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, the results showed that the average value of vocabulary mastery was 59.17 in the sufficient category and the average value of poetry writing ability was 50.89 in the less category. Then the results of the inferential analysis showed that the value of rcount (0.552) was greater than the value of rtable (0.329). Thus H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship between vocabulary mastery and the ability to write poetry in fifth grade students.